New potential biomarkers for early chronic kidney disease diagnosis in patients with different glucose tolerance status - Cassano, Velia; Pelaia, Corrado; Armentaro, Giuseppe; Miceli, Sofia; Tallarico, Valeria; Perini, Daniele Dallimonti; Fiorentino, Vanessa T.; Imbalzano, Egidio; Maio, Raffaele; Succurro, Elena; Hribal, Marta L.; Andreozzi, Francesco; et al. (Frontiers in Endocrinology, 2023)
The purpose of the present study was to investigate the role of oxidative stress, platelets activation and endocan levels in renal dysfunction, in normal glucose tolerance patients (NGT) with 1-hour plasma glucose values ≥ 155 mg/dL (NGT≥155), compared to NGT<155, impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM) newly diagnosed subjects. We enlisted 233 patients subjected to OGTT.The serum levels of platelets activation (Glycoprotein-VI and sP-selectin) oxidative stress biomarkers (8-isoprostane and Nox-2), and endocan were evaluated with ELISA test.Results: From NGT<155 to T2DM group, there was a statistically significant increase in 8-isoprostane (p<0.0001), Nox-2 (p<0.0001), Glycoprotein-VI (p<0.0001) and sP-selectin (p<0.0001) serum levels. Higher serum endocan levels were found with the worsening of metabolic profile (p<0.0001), specifically, NGT≥155 patients presented higher serum endocan values compared to NGT<155 (p<0.0001). From multivariate linear regression analysis, 1-h glucose resulted the major predictor of e-GFR justifying 23.6% of its variation (p<0.0001), 8-isoprostane and Nox-2 added respectively another 6.0% (p<0.0001) and 3.2% (p=0.001).Our study confirmed the link between 1-hour post-load glucose ≥155 mg/dl during OGTT and the possible increased risk for CKD, in newly diagnosed patients. The novelty is that we demonstrated a progressive increase in oxidative stress, platelets activation and serum endocan levels with the worsening of metabolic profile, which becomes evident early during the progression of CKD.